High-resolution mass spectrometry for thymosins detection and characterization. (July 2015) - Cabras, Tiziana; Iavarone, Federica; Martelli, Claudia; Delfino, Daniela; Rossetti, Diana Valeria; Inserra, Ilaria; Manconi, Barbara; Desiderio, Claudia; Messana, Irene; Hannappel, Ewald; Faa, Gavino; Castagnola, Massimo
<x xml:space="preserve">Abstract</x> Objectives: The aim of this study was to characterize β and α thymosins and their proteoforms in various tissues and bodily fluids by mass spectrometry and to look at their association with a wide variety of pathologies. Methods: A top–down proteomic platform based on high-performance liquid chromatography (HPLC) coupled to high-resolution LTQ-Orbitrap mass spectrometry (MS) was applied to the characterization of naturally occurring peptides. Results: In addition to thymosin β4 (Tβ4) and β10 (Tβ10), several post-translational modifications of both these peptides were identified not only in bodily fluids but also in normal and pathological tissues of different origins. The analysis of tissue specimens allowed the characterization of different C-terminal truncated forms of Tβ4 and Tβ10 together with other proteolytic fragments. The sulfoxide derivative of both Tβ4 and Tβ10 and the acetylated derivatives at lysine residues of Tβ4 were also characterized. Different proteoforms of prothymosin α, parathymosin α, thymosin α1 and thymosin α11 together with diverse proteolytic fragments were identified too. Conclusion: The clinical and prognostic significance and the origin of these proteoforms have to be deeply investigated.